Enhanced protective efficacy of nonpathogenic recombinant leishmania tarentolae expressing cysteine proteinases combined with a sand fly salivary antigen. - Farnaz Zahedifard; Elham Gholami; Tahereh Taheri; Yasaman Taslimi; Fatemeh Doustdari; Negar Seyed; Fatemeh Torkashvand; Claudio Meneses; Barbara Papadopoulou; Shaden Kamhawi; Jesus G Valenzuela; Sima Rafati (Public Library of Science (PLoS), 2014)
Novel vaccination approaches are needed to prevent leishmaniasis. Live attenuated vaccines are the gold standard for protection against intracellular pathogens such as Leishmania and there have been new developments in this field. The nonpathogenic to humans lizard protozoan parasite, Leishmania (L) tarentolae, has been used effectively as a vaccine platform against visceral leishmaniasis in experimental animal models. Correspondingly, pre-exposure to sand fly saliva or immunization with a salivary protein has been shown to protect mice against cutaneous leishmaniasis.Here, we tested the efficacy of a novel combination of established protective parasite antigens expressed by L. tarentolae together with a sand fly salivary antigen as a vaccine strategy against L. major infection. The immunogenicity and protective efficacy of different DNA/Live and Live/Live prime-boost vaccination modalities with live recombinant L. tarentolae stably expressing cysteine proteinases (type I and II, CPA/CPB) and PpSP15, an immunogenic salivary protein from Phlebotomus papatasi, a natural vector of L. major, were tested both in susceptible BALB/c and resistant C57BL/6 mice. Both humoral and cellular immune responses were assessed before challenge and at 3 and 10 weeks after Leishmania infection. In both strains of mice, the strongest protective effect was observed when priming with PpSP15 DNA and boosting with PpSP15 DNA and live recombinant L. tarentolae stably expressing cysteine proteinase genes.The present study is the first to use a combination of recombinant L. tarentolae with a sand fly salivary antigen (PpSP15) and represents a novel promising vaccination approach against leishmaniasis.